Concise review: role and function of the ubiquitin-proteasome system in mammalian stem and progenitor cells - Naujokat, Cord; Šarić, Tomo (Stem cells, 2007)
Highly ordered degradation of cell proteins by the ubiquitin-proteasome system, a sophisticated cellular proteolytic machinery, has been identified as a key regulatory mechanism in many eukaryotic cells. Accumulating evidence reveals that the ubiquitin-proteasome system is involved in the regulation of fundamental processes in mammalian stem and progenitor cells of embryonic, neural, hematopoietic, and mesenchymal origin. Such processes, including development, survival, differentiation, lineage commitment, migration, and homing, are directly controlled by the ubiquitin-proteasome system, either via proteolytic degradation of key regulatory proteins of signaling and gene expression pathways or via nonproteolytic mechanisms involving the proteasome itself or posttranslational modifications of target proteins by ubiquitin or other ubiquitin-like modifiers. Future characterization of the precise roles and functions of the ubiquitin-proteasome system in mammalian stem and early progenitor cells will improve our understanding of stem cell biology and may provide an experimental basis for the development of novel therapeutic strategies in regenerative medicine. Disclosure of potential conflicts of interest is found at the end of this article.
Gesehen am 19.02.2021